Child Abuse: Knowledge and Attitudes Among Pedodontics in Uberlandia e Araguari, Minas Gerais - Janaína Fernandes SANTOS; Karina Silva NUNES; Alessandro Leite CAVALCANTI; Edméia Costa e SILVA (Association of Support to Oral Health Research (APESB), 2006)
Objective: To identify from pediatric dentistry educational experiences and knowledge concerning child abuse/neglect, numbers of suspected cases of child abuse and knowledge of local child protection. Method: A survey with 26 pedodontics in Araguari and Uberlandia (Minas Gerais, Brazil) was done and they were sent a postal questionnaire, 17 responded, giving a 65.4 percent response rate. The survey requested demographic details, responses to possible physical abuse or neglect, and details of suspected child abuse reporting behavior. Results: In their working lives 52.9 percent said that they had seen a suspicious child physical abuse case; however, only 14.3 percent had reported a suspicious case to the authorities. Twenty-nine percent of dentists did not know their legal responsibility concerning reporting child abuse; and 61 percent did know where to report child abuse. Conclusion: Due to lack of training, most practitioners were unsure what to do in the event of a suspicion of child abuse. There is need for continuing education of dentistry practitioners regarding symptoms and signs of physical abuse and the role of dental team in the multidisciplinary management of child abuse. Dental curricula should be revisited to ensure that students are adequately prepared for this professional task.